2020
DOI: 10.3390/md18030159
|View full text |Cite
|
Sign up to set email alerts
|

Types and Distribution of Bioactive Polyunsaturated Aldehydes in a Gradient from Mesotrophic to Oligotrophic Waters in the Alborán Sea (Western Mediterranean)

Abstract: Polyunsaturated aldehydes (PUAs) are bioactive molecules suggested as chemical defenses and infochemicals. In marine coastal habitats, diatoms reach high PUA production levels during bloom episodes. Two fractions of PUA can usually be analyzed: pPUA obtained via artificial breakage of collected phytoplankton cells and dissolved PUA already released to the environment (dPUA). In nature, resource supply arises as a main environmental controlling factor of PUA production. In this work, we monitored the vertical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…both micro-and macroalgae). In addition, Bartual et al (2020) attested that µM ranges of dPUAs are expected to occur in the immediate vicinity of the producer cell, as occurred in this benthic environment, but disperse rapidly, consistently with pM to nM concentrations of dPUAs quantified in marine environments. A variety of aldehydes was putatively identified based on the mass spectra obtained at the three sampling times (Fig.…”
Section: Puas Dissolved In Seawatermentioning
confidence: 64%
See 1 more Smart Citation
“…both micro-and macroalgae). In addition, Bartual et al (2020) attested that µM ranges of dPUAs are expected to occur in the immediate vicinity of the producer cell, as occurred in this benthic environment, but disperse rapidly, consistently with pM to nM concentrations of dPUAs quantified in marine environments. A variety of aldehydes was putatively identified based on the mass spectra obtained at the three sampling times (Fig.…”
Section: Puas Dissolved In Seawatermentioning
confidence: 64%
“…It is worth considering that most of the previous studies focused only on the detection of three PUAs, i.e. heptadienal (C7:2), octadienal (C8:2), and decadienal (C10:2) (Vidoudez et al, 2011;Morillo-García et al, 2014;Ribalet et al, 2014;Wu and Li, 2016;Bartual et al, 2018;Bartual et al, 2020). Together with octatrienal (C8:3), C7:2 and C8:2 resulted the most abundant dPUA in coastal areas of the Adriatic Sea (Vidoudez et al, 2011;Ribalet et al, 2014); C7:2, C8:2, and C10:2 were also the most abundant in the northern South China Sea (Wu and Li, 2016), as similarly reported by Bartual et al (2018) in southwestern Spain.…”
Section: Puas Dissolved In Seawatermentioning
confidence: 99%
“…For example, compared with the samples stored for 60, 90, and 120 d, a greater aldehyde content was present in the initial sample (see Table 1 ), which is consistent with the findings of Duan [ 42 ]. It should be noted here that aldehydes possess a low flavor threshold in addition to a characteristic fat aroma at low concentrations [ 43 ]. In the fresh fish meat (i.e., at day 0), the key volatile organic compounds present (area A, Figure 6 ) were methylpropanal (D), methylpropanal (M), hexanal (D), hexanal (M), ethanol, 2-hexenal (M), and 2-methylbutanal (D).…”
Section: Results and Analysismentioning
confidence: 99%
“…A recent survey demonstrated that oxylipin pathways in diatoms were mostly based on the oxygenation of hexadecatrienoic, eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids, and, within phytoplankton communities, these secondary metabolites largely derived from diatoms [ 42 ]. Moreover, daily fluctuations of PUAs were more correlated to the cellular physiological state of diatoms than exclusively to the taxonomical composition of phytoplankton communities [ 43 ].…”
Section: Introductionmentioning
confidence: 99%